The effect of animated transitions on user navigation in 3D Tree-maps - Thomas Bladh; David A. Carr; Matjaž Kljun (IV'05: Proceedings of the International Conference on Information Visualisation, 2005)
This paper describes a user study conducted to evaluate the use of smooth animated transitions between directories in a three-dimensional, tree-map visualization. We looked specifically at the task of returning to a previously visited directory after either an animated or instantaneous return to the root location. The results of the study show that animation is a double-edged sword. Even though users take more shortcuts, they also make more severe navigational errors. It seems as though the promise of a more direct route to the target directory, which animation provides, somehow precludes users who navigate incorrectly from applying a successful recovery strategy.